COVID-19 infection among healthcare workers in an oncology hospital - Gülşen İskender; Duygu Mert; Zühal Avşar; Servet Kölgelier; Mustafa Ertek (Journal of Infection in Developing Countries)
Introduction: Healthcare workers are at high risk for acquiring COVID-19 and transmitting it to the patients especially to cancer patients in whom the risk of severe COVID-19 is high. We determined the rate of COVID-19 infection among healthcare workers in an oncology hospital and their epidemiological characteristics.